Um framework para apoiar o desenvolvimento de aplicações on-line acessíveis - Mahmud, Pablo Bizzi (Universidade Federal de São Carlos, 2016)
Through the increase of services that are now available online and with the diversity of the public that uses these services, the web begins to gain prominence as a mechanism capable of breaking down barriers and integrating users, connecting people of the most different economic classes and people with or without disabilities. With that in mind, we must rethink systems’ development guidelines so that they can be accessed by as many people as possible and reach the universal web. Helping developers make and provide accessible online applications, this work aims to develop a framework that serves as a basis for development, regardless of their skill of knowledge. Considering the current existence of organizations that standardize the development of accessible applications for people with disabilities, this work aims to cover all these recommendations in a tool to abstract all the programmer’s work review, creating accessible applications with minimal effort. In addition, this work presents the collection and validation of existing guidelines regarding the development of accessible applications in the web platform and their respective applications in the framework, as currently available guidelines are comprehensive in the development of accessible games. The tool, called ARIA-ACCESS, attests in its case study that it is easy to handle, even for beginner developers, and it presents a productivity gain regarding the development time, a result of the automatic generation of WAI-ARIA code.
Keywords: Acessibilidade; Framework; Accessibility; Online; Web; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO